The prokaryotic Argonaute proteins enhance homology sequence-directed recombination in bacteria. Issue 7 (30th January 2019) - Fu, Lei; Xie, Caiyun; Jin, Zehua; Tu, Zizhuo; Han, Li; Jin, Meilin; Xiang, Yaozu; Zhang, Anding
Abstract: Argonaute proteins are present and conserved in all domains of life. Recently characterized prokaryotic Argonaute proteins (pAgos) participates in host defense by DNA interference. Here, we report that the Natronobacterium gregoryi Argonaute ( Ng Ago) enhances gene insertions or deletions in Pasteurella multocida and Escherichia coli at efficiencies of 80–100%. Additionally, the effects are in a homologous arms-dependent but guide DNA- and potential enzyme activity-independent manner. Interestingly, such effects were also observed in other pAgos fragments including Thermus thermophilus Argonaute ( Tt Ago), Aquifex aeolicus Argonaute ( Aa Ago) and Pyrococcus furiosus Argonaute ( Pf Ago). The underlying mechanism of the Ng Ago system is a positive selection process mainly through its PIWI-like domain interacting with recombinase A (recA) to enhance recA-mediated DNA strand exchange. Our study reveals a novel system for enhancing homologous sequence-guided gene editing in bacteria.